A Test of Audit Deterrent to Financial Reporting Irregularities Using the Randomized Response Technique. - Schneider, Arnold; Wilner, Neil (The Accounting Review, 1990)
Describes an experiment that examines the effects of managers' perceptions of internal and external auditing on the potential commission of financial reporting irregularities. Deterrence effects of internal and external auditing; Use of quantitative randomized technique.